A pragmatic approach to ethical research collaboration with Indigenous communities: A case study with the Penan people of Long Lamai, Malaysia. Issue 1 (March 2023) - Dunaway, Michael; Allred, Shorna; Somchanhmavong, Amy Kuo; Zaman, Tariq
It is paramount that research relevant to Indigenous communities be conducted in partnership with them through free and prior informed consent. Historically, much research was extractive in nature, performed without Indigenous community consent, and often applied a deficit-framing. Some academic professional societies have developed guidelines for ethically conducting research with Indigenous communities to avoid these unethical practices. However, missing from these ethical research declarations are the specifics on research implementation or how research can be enriched through an ethical research approach. In 2010, the Association of American Geographers' (AAG, now known as the American Association of Geographers) Indigenous Peoples Specialty Group (IPSG) wrote a Declaration of Key Questions About Research Ethics with Indigenous Communities outlining several questions that researchers should ask themselves when collaborating with Indigenous communities. We selected the AAG's ethical principles for this study as it was one of the first environmentally oriented professional societies to make such a declaration. It is also among the world's largest professional societies with over 10, 000 members across 100 countries, with nearly upward of 7000 in attendance at its annual conference. The IPSG's Declaration organizes their key questions around several elements: (1) Formulating the Project, (2) Identities of the Researchers, (3) Partnerships, (4) Benefits, (5) Findings, and (6) Deepening Relationships. This article discusses how each of the elements in the IPSG's Declaration can be addressed for a wide range of research projects, providing specific examples from the Global Citizenship and Sustainability (GCS) program, a community-based partnership between Cornell University, the Institute of Social Informatics and Technological Innovations at the Universiti Malaysia Sarawak, and Penan village leaders in Long Lamai, Malaysia. This article argues that GCS' research was enhanced through a non-extractive, community-based, and collaborative research mindset and further describes questions based on the IPSG's Declaration that researchers can ask themselves throughout their research processes. This article serves as a foundation for researchers collaborating with Indigenous communities to think about their research to give agency to those communities while conducting innovative research. This article has been written in consultation with a community-chosen representative of Long Lamai, Borneo.